FAKTOR-FAKTOR YANG MEMPENGARUHI TURNOVER INTENTION KARYAWAN PADA PT BINTANG SEJAHTERA BATAM GROUP - Yunita, Yunita; Nainggolan, Nora Pitri (SCIENTIA JOURNAL, 2021)
To be able to compete and survive, distributor companies must optimize its human resource management which is the backbone of the company. Company negligence regarding this can cause various threats to the company, one of which is turnover intention This study aims to test the influence of job satisfaction, organizational commitment and job stress on employee turnover intention at PT Bintang Sejahtera Batam Group by using saturation sampling with 103 respondents. Data collected using questionnaire with Likert scale measurement. Data analysis method used in this study are descriptive analysis, validity test, reliability test, multiple linear regression analysis, determination coefficient analysis (R2), t test and F test. Then the data was processed using SPSS version 26 program. Based on t test results, it shows that job satisfaction has a significant effect on turnover intention with a sig value of 0.013 < 0.05, organizational commitment has a significant effect on turnover intention with a sig value of 0.039 <0.05 and job stress has a significant effect on turnover intention with a sig value of 0.002< 0.05. Based on F test result, job satisfaction, organizational commitment, and job stress simultaneously have a significant effect on turnover intention with a sig value of 0.000<0.05. Keywords: Job Satisfaction; Organizational Commitment; Job Stress; Turnover Intention.